Numerical methods and error estimates for a singular boundary‐value problem - Lima, P. M.; Oliveira, A. M. (Mathematical Modelling and Analysis, 2002)
In this paper we analyze a class of equations of the form y? (x) = —g(x) xp (y(x)) q where p and q are real parameters satisfying p > _1 , g